(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2017)
حقق القطاع المصرفي السوري خلال سنوات الأزمة السورية أرباح اًيعود القسم الأكبر منها إلى التغير المستمر لسعر الليرة السورية مقابل العملات الأجنبية. ولأن عملية تحديد النمو تتطلب مراقبة تطور العديد من العناصر الأساسية في عمل المصرف,عندها يمكن القول بأنه منذ بداية الأزمة وحتى الآن, واستناداً إلى التقارير السنوية للمصارف السورية,لم يحقق القطاع المصرفي أي نمو حقيقي. ويعد ذلك طبيعياً مع مرور البلاد بأقسى الأوقات والظروف, مما جعل العجلة الاقتصادية تنحدر بشكل ملحوظ. يهدف البحث إلى دراسة تطور الابتكار في الخدمة المصرفية وتأثير ذلك على الأداء التسويقي. ولتحقيق ذلك استخدمت الباحثة نموذج الأبعاد الستة لابتكار الخدمات لتقييم الأداء التسويقي وتمت صياغة ثلاثة فرضيات رئيسة, تم اختبارها بواسطة الرزمة الإحصائية للعلوم الاجتماعيةStatistical Package for Social Sciences,SPSS V(23), لتتوصل الباحثة إلى عدة نتائج أهمّها: يتفوق بنك بيمو على المصرف التجاري السوري في درجة تبنيه للابتكار كاستراتيجية خلال فترة الأزمة,ولا توجد علاقة معنوية بين الابتكار في الخدمات والأداء التسويقي. واقترحت الباحثة دراسة الفرص التي أفرزتها الأزمة من خلال تحليل البيئة الداخلية والخارجية للمصارف,والاعتماد على أنشطة الابتكار كاستراتيجية للاستثمار الأمثل والنمو طويل الأجل. The Syrian banking sector has achieved profits during the Syrian crisis, the bulk of it is due to the revaluation of foreign currencies into SYP using the new exchange rates. The process of identifying growth requires monitor the development of many of the basic elements of the Bank’s work, So we can say that Since the beginning of the crisis so far, based on the annual reports of Syrian banks, the banking sector did not achieve any real growth.That is normal causeThe country is going through one of its most difficult times, making the economic wheel descend significantly. The research aims to study the development of innovations in banking service and their impact on marketing performance.To achieve this, the researcher used the model of six dimensions of innovation services to assess marketing performance, and has been formulated three main hypotheses were tested by Statistical Package for Social Sciences SPSS V (23) to reach the researcher to several conclusions, including: Bank Bemo outperform the Commercial Bank of Syria in the degree of innovation strategy adopted during the crisis, and there is no significant relationship between innovationin services and marketing performance.so,the researcher has proposed to study the opportunities which are created by the crisis through analyzing the internal and external environment of banks, relying on innovation activities as a strategy for optimization investment and long-term growth.